A Systematic Approach To Digital Gambling: The Role Of Accounting Information Systems In Economic Stabilization - Windy Dwiparaswati; Wahyu Widjayanti (Asosiasi Dosen Muda Indonesia, 2025)
The rapid rise of digital betting in Indonesia has led to significant economic impacts, particularly on household financial stability and the national economy. Although digital betting is illegal in Indonesia, the ease of access to digital platforms has led to its widespread growth, with transaction values estimated to reach IDR 327 trillion by 2023. This study aims to explore the economic impacts of digital betting and how Accounting Information Systems (AIS) can play a crucial role in managing and mitigating the financial losses caused by this phenomenon. Using a descriptive qualitative approach, data were collected through literature reviews and secondary data analysis from official reports and trusted sources. The findings show that digital betting contributes to financial instability in households, increased debt, decreased work productivity, and the diversion of spending from essential needs. Additionally, this study highlights the importance of implementing AIS to monitor betting-related cash flows, increase financial transparency, and provide relevant data for policymakers to design preventive measures. The study suggests stronger policies to regulate digital betting and recommends leveraging AIS as a tool to foster economic stability at both individual and community levels.